Stapled peptide PROTAC induced significantly greater anti-PD-L1 effects than inhibitor in human cervical cancer cells - Shi, Yu-Ying; Wang, An-Jin; Liu, Xue-Lian; Dai, Meng-Yuan; Cai, Hong-Bing (Frontiers in Immunology, 2023)
Immune checkpoint inhibitors (ICIs) are monoclonal antibodies that target immune checkpoints that suppress immune cell activity. Low efficiency and high resistance are currently the main barriers to their clinical application. As a representative technology of targeted protein degradation, proteolysis-targeting chimeras (PROTACs) are considered to have potential for addressing these limitations. We synthesized a stapled peptide-based PROTAC (SP-PROTAC) that specifically targeted palmitoyltransferase ZDHHC3 and resulted in the decrease of PD-L1 in human cervical cancer cell lines. Flow cytometry, confocal microscopy, protein immunoblotting, Cellular Thermal Shift Assay (CETSA), and MTT assay analyses were conducted to evaluate the effects of the designed peptide and verify its safety in human cells.In cervical cancer cell lines C33A and HeLa, the stapled peptide strongly downregulated PD-L1 to < 50% of baseline level at 0.1 μM. DHHC3 expression decreased in both dose-dependent and time-dependent manners. MG132, the proteasome inhibitor, can alleviate the SP-PROTAC mediated degradation of PD-L1 in human cancer cells. In a co-culture model of C33A and T cells, treatment with the peptide induced IFN-γ and TNF-α release in a dose-dependent manner by degrading PD-L1. These effects were more significant than that of the PD-L1 inhibitor, BMS-8. Cells treated with 0.1 μM of SP-PROTAC or BMS-8 for 4 h revealed that the stapled peptide decreased PD-L1 more effectively than BMS-8. DHHC3-targeting SP-PROTAC decreased PD-L1 in human cervical cancer more effectively than the inhibitor BMS-8.